Gaia data release 1 - open cluster astrometry: performance, limitations, and future prospects - Leeuwen, Floor van; Bastian, Ulrich; Biermann, Michael; Grebel, Eva K.; Els, Sebastian; Altmann, Martin; Hauser, Marcus; Jordan, Stefan; Hofmann, Wilfried; Lenhardt, Helmut; Mantelet, Grégory (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics